Concentrated Ownership and Corporate Social Responsibility: Insights from Indian Companies - Potharla, Srikanth (The Indonesian Journal of Accounting Research, 2023)
This study examined the complex relationship between ownership structures, family business dynamics, group affiliations, and Corporate Social Responsibility (CSR) expenditures on the Indian market from 2010 to 2022. Using 10,684 observations representing 1,882 Indian companies, this study analyzed block-holder investment size, coalition effect, and contestability factors. This study hypothesized and found empirical evidence indicating that family businesses with substantial promoter holdings allocate fewer resources to CSR, primarily due to their propensity to maintain control and conserve resources. In addition, the study reveals the significant effects of power dynamics within organizations, competitive landscapes, and group affiliations on CSR initiatives. The findings are important to various stakeholders, including retail and institutional investors, government bodies, non-governmental organizations, consumers, and suppliers, as they provide insights to advance responsible business practices and foster a more sustainable and socially responsible business environment.